Organocatalytic tandem Michael addition reactions: A powerful access to the enantioselective synthesis of functionalized chromenes, thiochromenes and 1,2-dihydroquinolines - Bhanja, Chittaranjan; Jena, Satyaban; Nayak, Sabita; Mohapatra, Seetaram (Beilstein Journal of Organic Chemistry, 2012)
Enantioselective organocatalysis has become a field of central importance within asymmetric chemical synthesis and appears to be efficient approach toward the construction of complex chiral molecules from simple achiral materials in one-pot transformations under mild conditions with high stereocontrol. This review addresses the most significant synthetic methods reported on chiral-amine-catalyzed tandem Michael conjugate addition of heteroatom-centered nucleophiles to α,β-unsaturated compounds followed by cyclization reactions for the enantioselective construction of functionalized chiral chromenes, thiochromenes and 1,2-dihydroquinolines in optically enriched forms found in a myriad of bioactive natural products and synthetic compounds.
Keywords: chromenes; 1,2-dihydroquinolines; enantioselective; Michael addition; organocatalytic; thiochromenes